Virtual Screen for Repurposing of Drugs for Candidate Influenza a M2 Ion-Channel Inhibitors - Radosevic, Draginja; Sencanski, Milan; Perovic, Vladimir; Veljkovic, Nevena; Prljic, Jelena; Veljkovic, Veljko; Mantlo, Emily; Bukreyeva, Natalya; Paessler, Slobodan; Glisic, Sanja (Frontiers in Cellular and Infection Microbiology, 2019)
Influenza A virus (IAV) matrix protein 2 (M2), an ion channel, is crucial for virus infection, and therefore, an important anti-influenza drug target. Adamantanes, also known as M2 channel blockers, are one of the two classes of Food and Drug Administration-approved anti-influenza drugs, although their use was discontinued due to prevalent drug resistance. Fast emergence of resistance to current anti-influenza drugs have raised an urgent need for developing new anti-influenza drugs against resistant forms of circulating viruses. Here we propose a simple theoretical criterion for fast virtual screening of molecular libraries for candidate anti-influenza ion channel inhibitors both for wild type and adamantane-resistant influenza A viruses. After in silico screening of drug space using the EIIP/AQVN filter and further filtering of drugs by ligand based virtual screening and molecular docking we propose the best candidate drugs as potential dual inhibitors of wild type and adamantane-resistant influenza A viruses. Finally, guanethidine, the best ranked drug selected from ligand-based virtual screening, was experimentally tested. The experimental results show measurable anti-influenza activity of guanethidine in cell culture.